Applications of XRF, NAA and low-kV radiographic techniques in the study of body composition and diseased tissue - Bradley, D.A.; Ng, K.H.; Green, S.; Mountford, P.J.; Shukri, A.; Evans, J. (Faculty of Medicine, University of Malaya, 1996)
Members of this group have responded to a number of challenging health issues by attempting to devise sensitive XRF, NAA and low-kV radiographic measurement systems for both in vivo and in vitro applications. These studies are generally either of toxicological importance, examine potential for diagnosing the presence of disease, or offer effective means for monitoring potentially harmful side-effects of therapy. Particular examples include the in vivo XRF investigation of human skeletal uptake of Pb in working and living environments, in vivo XRF monitoring of elevated levels of Fe in skin (indicating the presence of an undesirable side-effect of the treatment of thalassaemia), in vivo NAA monitoring of elevated levels of Al in bone (indicating an undesirable side-effect of the treatment of chronic renal failure) and in vitro characterization, by means of low-kV imaging, of a range of calcification parameters in healthy and diseased breast tissue. The latter investigation has been conducted in association with an in vitro NAA study of concentrations of trace elements in the same types of tissue. Figures of merit for the various measurement systems have been obtained in terms of minimum detectable levels and concentrations (MDL's and MDC's) and where applicable, image related parameters.